Area expansion of the city of architecture (Journal of the College of Basic Education, 2023)
Summary of the research:This study is based on knowledge of the spatial expansion of the city of Amarah, due to the conditions that Iraq in general and the city of Amara in particular went through, due to the migration of large numbers of residents from the countryside to the city and migration from other governorates, which the city witnessed unusual developments in the economic, social and demographic characteristics of its population on the one hand. On the other hand, its functional structure. In view of the city's rapid urban expansion and a remarkable increase in the population. This led to an increase in the population, which eventually led to the transformation of most of the agricultural lands into residential lands.Keywords: expansion, city, determinants.